WAT sampling, general diets info, fatty acids in diets, fatty acids in WAT, body mass and tail girth data, glmm from HF/C group from Of fruits and fats: high-sugar diets restore fatty acid profiles in the white adipose tissue of captive dwarf lemurs - M. B. Blanco; L. K. Greene; L. Ellsaesser; B. Schopler; M. Davison; C. Ostrowski; P. H. Klopfer; J. Fietz; E. E. Ehmke (2022)
Fat-storing hibernators rely on fatty acids from white adipose tissue (WAT) as an energy source to sustain hibernation. Whereas Arctic and temperate hibernators preferentially recruit dietary polyunsaturated fatty acids (PUFAs), tropical hibernators can rely on monounsaturated fatty acids that produce fewer lipid peroxides during oxidation. Nevertheless, compositional data on WAT from tropical hibernators are scant and questions remain regarding fat recruitment and metabolism under different environmental conditions. We analyze fatty acid profiles from the WAT of captive dwarf lemurs ( Cheirogaleus medius ) subjected to high-sugar or high-fat diets during fattening and cold or warm conditions during hibernation. Dwarf lemurs fed high-sugar, compared to high-fat, diets displayed WAT profiles more comparable to wild lemurs that fatten on fruits and better depleted their fat reserves during hibernation. One PUFA, linoleic acid, remained elevated before hibernation, potentially lingering from the diets provisioned prior to fattening. That dwarf lemurs preferentially recruit the PUFA linoleic acid from diets that are naturally low in availability could explain the discrepancy between captive and wild lemurs' WAT. While demonstrating that minor dietary changes can produce major changes in seasonal fat deposition and depletion, our results highlight the complex role for PUFA metabolism in the ecology of tropical hibernators.